THE FUNCTION OF INDUSTRIAL CONTROLLERSHIP. - Anderson, David R. (The Accounting Review, 1944)
Abstract The controllership function is in a state of evolution and development, and that there is a truly amazing variety in the nature and scope of controller's duties and the importance of his job in different companies. In most business enterprises the organization of responsibilities tends to vary with capacities, and perhaps with interests, of individuals who make up the executive "team," and, furthermore, that the higher one goes in the scale of responsibilities, the more likely one is to find this kind of variation. This is an inevitable and a desirable condition, for it is usually easier to adapt organization to human capacities than to attempt to mold people to fit a rigid organization plan. This process of adaptation cannot be carried too far, as there are certain principles of organization which are basic and which must be observed in management is to function effectively, but the area of possible variation is rather broad. And so it is often found controllers performing duties which seem to be clearly extraneous to their function as it is generally understood, and in many cases it seems that these duties are assigned to them simply for lack of a better place in the organization to unload them.